2017
DOI: 10.1111/mec.14395
|View full text |Cite
|
Sign up to set email alerts
|

Environmental DNA detection of rare and invasive fish species in two Great Lakes tributaries

Abstract: The extraction and characterization of DNA from aquatic environmental samples offers an alternative, noninvasive approach for the detection of rare species.Environmental DNA, coupled with PCR and next-generation sequencing ("metabarcoding"), has proven to be very sensitive for the detection of rare aquatic species. Our study used a custom-designed group-specific primer set and nextgeneration sequencing for the detection of three species at risk (Eastern Sand Darter, Ammocrypta pellucida; Northern Madtom, Notur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 76 publications
0
71
0
Order By: Relevance
“…While many studies have shown the advantages of using eDNA metabarcoding in lotic (flowing streams and rivers; Balasingham et al ., ) and lentic (still lakes and ponds; (Hänfling et al ., ; Harper et al ., ) systems, they also raise concerns about the influence of flow in DNA dispersal in fast running water and the need to sample multiple locations in lentic waters. Canals represent man‐made environments with a semi‐lotic regime and regulated flow, which minimise the risk of detection of species present too far away, while at the same time allowing enough water movement to reduce the need for extra sampling akin to that undertaken in lentic systems.…”
mentioning
confidence: 99%
“…While many studies have shown the advantages of using eDNA metabarcoding in lotic (flowing streams and rivers; Balasingham et al ., ) and lentic (still lakes and ponds; (Hänfling et al ., ; Harper et al ., ) systems, they also raise concerns about the influence of flow in DNA dispersal in fast running water and the need to sample multiple locations in lentic waters. Canals represent man‐made environments with a semi‐lotic regime and regulated flow, which minimise the risk of detection of species present too far away, while at the same time allowing enough water movement to reduce the need for extra sampling akin to that undertaken in lentic systems.…”
mentioning
confidence: 99%
“…Given that detection probabilities tend to increase when multiple conventional methods are used, they would presumably also increase if multiple non‐harmful methods are employed. Another non‐harmful method that could be used with underwater cameras, and is becoming increasingly popular for detecting rare aquatic species, is environmental DNA (eDNA; Balasingham, Walter, Mandrak, & Heath, ; Boothroyd, Mandrak, Fox, & Wilson, ; Janosik & Johnson, ). This emerging method detects species based on collected genetic material from water samples (Janosik & Johnson, ), but also has some limitations, such as the heterogeneous distribution of eDNA across temporal and spatial scales in a river, reducing the detection of species even at small spatial scales (Macher & Leese, ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a target species can be estimated by detecting the eDNA in water samples instead of locating or capturing individuals (Lodge et al, ). These advantages have enabled noninvasive, quick, and wide‐ranging assessments of the presence/absence of species and their biodiversity and abundance in freshwater (Balasingham, Walter, Mandrak, & Heath, ; Bista et al, ; Deiner, Fronhofer, Mächler, Walser, & Altermatt, ; Fukumoto, Ushimaru, & Minamoto, ; Yamanaka & Minamoto, ) and marine environments (Boussarie et al, ; Lacoursière‐Roussel et al, ; Sigsgaard et al, ; Thomsen, Kielgast, Iversen, Møller, et al, ; Thomsen, Kielgast, Iversen, Wiuf, et al, ; Yamamoto et al, ).…”
Section: Introductionmentioning
confidence: 99%